PhoH2 proteins couple RNA helicase and RNAse activities. (7th January 2020) - Andrews, Emma S. V.; Arcus, Vickery L.
Abstract: PhoH2 proteins are found in a very diverse range of microorganisms that span bacteria and archaea. These proteins are composed of two domains: an N‐terminal PIN‐domain fused with a C‐terminal PhoH domain. Collectively this fusion functions as an RNA helicase and ribonuclease. In other genomic contexts, PINdomains and PhoHdomains are separate but adjacent suggesting association to achieve similar function. Exclusively among the mycobacteria, PhoH2 proteins are encoded in the genome with an upstream gene, phoAT, which is thought to play the role of an antitoxin (in place of the traditional VapB antitoxin that lies upstream of the 47 other PINdomains in the mycobacterial genome). This review examines PhoH2 proteins as a whole and describes the bioinformatics, biochemical, structural, and biological properties of the two domains that make up PhoH2: PIN and PhoH. We review the transcriptional regulators of phoH2 from two mycobacterial species and speculate on the function of PhoH2 proteins in the context of a Type II toxin–antitoxin system which are thought to play a role in the stress response in bacteria.